2011
DOI: 10.1139/p11-037
|View full text |Cite
|
Sign up to set email alerts
|

Shock pattern solutions for viscous-collisional plasma ion acoustic waves in view of the linear theory of the non-equilibrium thermodynamics

Abstract: In the framework of irreversible thermodynamics, we study nonlinear ion-acoustic waves (IAWs) in viscous and collisional plasmas. Electrons, which form the background, are assumed to be nonthermal. On account of ion viscosity and ion-electron collisions, we investigate using ion fluid equations. We study the effects of the nonthermally distributed electrons β and the temperature ratio σ (= Ti/Te) on the stability, where the stability for Burger’s equation is analyzed by two methods: the phase portrait method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…13 Theoretical studies on the effect of viscosity on the ion-acoustic solitary wave are carried out in general by using the reductive perturbation method or the Sagdeev's approach. [14][15][16][17][18] In fact, it has been known that viscosity can modify the solitary wave structure. Shukla has shown that inclusion of the ion viscosity change the structure of the ionacoustic solitary wave.…”
Section: Introductionmentioning
confidence: 99%
“…13 Theoretical studies on the effect of viscosity on the ion-acoustic solitary wave are carried out in general by using the reductive perturbation method or the Sagdeev's approach. [14][15][16][17][18] In fact, it has been known that viscosity can modify the solitary wave structure. Shukla has shown that inclusion of the ion viscosity change the structure of the ionacoustic solitary wave.…”
Section: Introductionmentioning
confidence: 99%